The Influence of Service Quality, Promotion, and Secure Transaction Towards Purchase Decision (Study Case on Tokopedia.com) - Maria Rosita Purwaningrum; Lamhot Henry Pasaribu (Enrichment : Journal of Management, 2021)
In the current digital era, shopping through the e-commerce will be more convenient and efficient. Many online shops appear in social media where the security is not guaranteed. This study aims to see how much is the influence of quality service, promotion and secure transaction towards purchase decision at Tokopedia. The numbers of visitors that have been decreasing throughout 2020 was the main reason to have this research, where one of its competitors finally defeated Tokopedia. The research model is a modification and a novelty of previous research, which in previous studies only used variables of service quality, promotion and purchase decision. The addition or novelty of this reaserch is to add a secure transaction variable as the dependent variable. This research is an explanatory research with non-probability sampling that uses a snowball system to distribute the questionnaire. This research was conducted towards specific respondents, which is a graduate college student in the Jabodetabek area. Promotion and secure transaction are proven to have a positive and significant influence on purchase decision at Tokopedia. The variable of service quality, it is not proven to have an influence on purchase decision at Tokopedia, especially among postgraduate students in the Jabodetabek area.